2016
DOI: 10.1186/s12933-016-0386-5
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically-inactive glucagon-like peptide-1(9–36)amide confers selective protective actions against post-myocardial infarction remodelling

Abstract: BackgroundGlucagon-like peptide-1 (GLP-1) therapies are routinely used for glycaemic control in diabetes and their emerging cardiovascular actions have been a major recent research focus. In addition to GLP-1 receptor activation, the metabolically-inactive breakdown product, GLP-1(9–36)amide, also appears to exert notable cardiovascular effects, including protection against acute cardiac ischaemia. Here, we specifically studied the influence of GLP-1(9–36)amide on chronic post-myocardial infarction (MI) remode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…It has been suggested that GLP-1(9-36)NH 2 may have effects on glucose homeostasis [43] and on the cardiovascular system [44][45][46]. In rodents, fragments of the GLP-1 metabolite may also have glucoregulatory effects, possibly mediated through hepatocytes [39], in line with previous observations of degradation of the GLP-1 metabolite [10,40].…”
Section: Discussionsupporting
confidence: 70%
“…It has been suggested that GLP-1(9-36)NH 2 may have effects on glucose homeostasis [43] and on the cardiovascular system [44][45][46]. In rodents, fragments of the GLP-1 metabolite may also have glucoregulatory effects, possibly mediated through hepatocytes [39], in line with previous observations of degradation of the GLP-1 metabolite [10,40].…”
Section: Discussionsupporting
confidence: 70%
“…Similarly, continuous infusion of GLP-1(9-36), 25 nmol/kg/day for 4 weeks, in female C57BL/6 mice following permanent left anterior descending coronary artery ligation did not modify body weight, plasma glucose, or infarct size. However, the extent of diastolic dysfunction was significantly attenuated, and pro-inflammatory cytokine expression and macrophage infiltration were reduced in hearts of GLP-1(9-36)amide-treated mice (Robinson et al, 2016). Although mechanisms linking GLP-1(9-36) or GLP-1(28-36) to improved ventricular function remain poorly defined, direct cardioprotective actions of GLP-1(9-36) remain evident in hearts or CMs from Glp1r À/À mice (Ban et al, 2008(Ban et al, , 2010.…”
Section: In the Heart And Blood Vesselsmentioning
confidence: 93%
“…GLP‐1R mediates most, if not all of the biological effects of GLP‐1 (7–36) amide (Campbell & Drucker, ; During et al, ). In contrast, whether GLP‐1 (9–36) functions through GLP‐1R remains unclear (Ban et al, ; Nikolaidis et al, ; Poudyal, ; Robinson et al, ). To further elucidate mechanisms associated with the LTP‐enhancing effects by GLP‐1 (9–36), we co‐administered (via i.p.…”
Section: Resultsmentioning
confidence: 99%
“…3.6 | The enhancement of hippocampal LTP induced by GLP-1 (9-36) treatment in vivo is blunted with administration of GLP-1 receptor antagonist exendin (9-39)amide GLP-1R mediates most, if not all of the biological effects of GLP-1 (7-36) amide (Campbell & Drucker, 2013;During et al, 2003). In contrast, whether GLP-1 (9-36) functions through GLP-1R remains unclear (Ban et al, 2008;Nikolaidis et al, 2005;Poudyal, 2016;Robinson et al, 2016). To further elucidate mechanisms associated with the LTPenhancing effects by GLP-1 (9-36), we co-administered (via i.p.…”
Section: Glp-1 (9-36) Administration In Vivo Leads To Suppression Omentioning
confidence: 99%
See 1 more Smart Citation